Evaluasi Program Angkutan Publik Berbasis Listrik: Studi Kasus Bus Trans Semanggi Suroboyo - Vidy Vicesa Alviyah; Rodiyah, Isnaini (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to evaluate the performance of the Trans Semanggi Suroboyo Bus Electric-Based Public Transport Program in the City of Surabaya. The research method used is a qualitative approach with data collection techniques in the form of interviews and direct observation. The evaluation was carried out using William N. Dunn's evaluation model which consists of six criteria, namely effectiveness, efficiency, adequacy, equity, responsiveness and accuracy. The evaluation results show that the achievements of the Trans Semanggi Suroboyo program are still relatively low in terms of number of passengers and contribution to reducing CO2 emissions. However, Trans Semanggi electric buses have proven to be more efficient than petrol/diesel buses. Recommendations for improving the quality and integration of public transportation modes in the City of Surabaya include better coordination between bus operators, increasing the number of fleets, expanding operational routes, and increasing the quality of responsiveness. This study has high relevance to the urgency of comprehensive evaluation of the performance of environmentally friendly transportation programs to ensure the various expected benefits and positive impacts are achieved.